GLOBALISATION AND INDIAN SCHOOL EDUCATION: IMPACT AND CHALLENGES - Meenu Anand (European Scientific Journal, ESJ, 2015)
Globalization is an important phenomenon that has affected the entire world in the contemporary era. Its impact on the education system of a country is intrinsic. In the context of India, globalization has impacted upon the education system in complex and conflicting ways. There is an increased emphasis on preparing global citizens who are ready to face the highly competitive world. There is a huge upsurge in the demand for learning English language, growing popularity of international schools, need for curriculum restructuring and inclusion of ICTs etc. While the basic aims of education are to enable children develop their potentials, define and pursue a meaningful purpose; globalisation has put an extra pressure on the education system to create ‘winners’ who are ready to battle in the race for the survival of the fittest. The present paper is an attempt to unveil the impact of globalisation on the school system as a whole. The paper is based on an empirical research conducted in sixteen government and private schools of Delhi, India. It explores their overall resources- physical infrastructure, human and non-human assets and various facilities that are intrinsic in order to provide quality education to the children. It attempts to present the contrasting revelations across the two categories of school education with respect to diverse variables such as strength of teachers and pupils, available infrastructure and its maintenance, co-curricular activities etc. It dwells into an investigation of attempts by the schools to provide a pro-social learning environment to pupils for indulging in innovative and creative accomplishments and providing a platform to explore and nurture their hidden talents. An interesting component that emerges is the strident diversity in the broad Art Education and Health and Physical Education school activities that are indeed significant for overall personality development. It also seeks to compare and critique the two categories of schools in terms of their inherited inequalities and explore their efforts as well as challenges to provide high standards of education. Last but not the least, the paper links the outcomes of the research with globalisation. It seeks to suggest few areas significant for developing an ideal knowledge base for a global education within the contemporary Indian school system keeping in mind the child and human rights perspective.